Mitochondria-specific drug release and reactive oxygen species burst induced by polyprodrug nanoreactors can enhance chemotherapy - Zhang, Wenjia; Hu, Xianglong; Shen, Qi; Xing, Da (Nature communications, 2019)
Cancer cells exhibit slightly elevated levels of reactive oxygen species (ROS) compared with normal cells, and approximately 90% of intracellular ROS is produced in mitochondria. In situ mitochondrial ROS amplification is a promising strategy to enhance cancer therapy. Here we report cancer cell and mitochondria dual-targeting polyprodrug nanoreactors (DT-PNs) covalently tethered with a high content of repeating camptothecin (CPT) units, which release initial free CPT in the presence of endogenous mitochondrial ROS (mtROS). The in situ released CPT acts as a cellular respiration inhibitor, inducing mtROS upregulation, thus achieving subsequent self-circulation of CPT release and mtROS burst. This mtROS amplification endows long-term high oxidative stress to induce cancer cell apoptosis. This current strategy of endogenously activated mtROS amplification for enhanced chemodynamic therapy overcomes the short lifespan and action range of ROS, avoids the penetration limitation of exogenous light in photodynamic therapy, and is promising for theranostics. Mitochondria are a source of reactive oxygen species, which can be exploited to induce the death of cancer cells. Here, the authors use nanoparticles that release camptothecin in a reactive oxygen species dependent manner, leading to cancer cell death.